Factors influencing the implementation of screening and brief interventions for alcohol use in primary care practices: a systematic review using the COM-B system and Theoretical Domains Framework - Rosário, Frederico; Santos, Maria Inês; Angus, Kathryn; Pas, Leo; Ribeiro, Cristina; Fitzgerald, Niamh (Springer Nature, 2021)
Background Alcohol is a leading risk factor contributing to the global burden of disease. Several national and international agencies recommend that screening and brief interventions (SBI) should be routinely delivered in primary care settings to reducing patients’ alcohol consumption. However, evidence shows that such activities are seldom implemented in practice. A review of the barriers and facilitators mediating implementation, and how they fit with theoretical understandings of behaviour change, to inform the design of implementation interventions is lacking. This study aimed to conduct a theory-informed review of the factors influencing general practitioners’ and primary care nurses’ routine delivery of alcohol SBI in adults. Methods A systematic literature search was carried out in four electronic databases (Medline, CINAHL, CENTRAL, PsycINFO) using comprehensive search strategies. Both qualitative and quantitative studies were included. Two authors independently abstracted and thematically grouped the data extracted. The barriers and facilitators identified were mapped to the domains of the Capability-Opportunity-Motivation-Behaviour system/Theoretical Domains Framework (TDF). Results Eighty-four out of the 258 studies identified met the selection criteria. The majority of the studies reported data on the views of general practitioners (n = 60) and used a quantitative design (n = 49). A total of 660 data items pertaining to barriers and 253 data items pertaining to facilitators were extracted and thematically grouped into 46 themes. The themes mapped to at least one of the 14 domains of the TDF. The three TDF domains with the highest number of data units coded were ‘Environmental Context and Resources’ (n = 158, e.g. lack of time), ‘Beliefs about Capabilities’ (n = 134, e.g. beliefs about the ability to deliver screening and brief advice and in helping patients to cut down) and ‘Skills’ (n = 99, e.g. lack of training). Conclusions This study identified a range of potential barriers and facilitators to the implementation of alcohol SBI delivery in primary care and adds to the scarce body of literature that identifies the barriers and facilitators from a theoretical perspective. Given that alcohol SBI is seldom implemented, this review provides researchers with a tool for designing novel theory-oriented interventions to support the implementation of such activity.
Keywords: Research Subject Categories::MEDICINE::Psychiatry::Addiction medicine